Internalisasi Nilai-Nilai Pendidikan Agama Islam dalam Memperkokoh Negara Kesatuan Republik Indonesia - Mohammad Fahrur Rozi (Proceedings of Annual Conference for Muslim Scholars, 2017)
Abstract: Indonesia is also known as a country that has a lot of religion, ethnicity, culture and language. In reality, Indonesia has not quite able to manage the plurality properly, therefore was born conflict and violence can be threat the Homelands security. In aspect of education, Indonesia began by tinged with some of students as a generation of people involved in brawls, using drug, crime and even worse, the impression of Western poisoning (westoxification) on the minds of the Muslims. In this regard, the internalization of the values of Islamic religious education in strengthening the Homelands is required by the institution as an alternative bids through by the transformation of Islamic values such as: approach indoctrination, approach to moral reasoning and approach to forecasting consequence for beloved Republic of Indonesia (Homeland) beloved.Keywords: Internalization, values of Islamic religious, Republic of Indonesia (Homeland)